Development of Interactive Multimedia using Google Sites and Problem-Based Learning to Improve Numeracy in Trigonometry for 10th Grade Students - Nuria Amanda; Sri Winarni; Rohati Rohati (MASI Mandiri Edukasi, 2025)
Interactive multimedia based on Problem-Based Learning (PBL) is a digital teaching medium that combines multimedia elements such as text, images, audio, video, and animations with the PBL learning model approach using Google Sites. This research aims to produce interactive multimedia based on Problem-Based Learning (PBL) utilizing Google Sites to enhance numeracy skills in trigonometry material for 10th-grade high school students. This research uses a descriptive qualitative approach with the Research and Development (R&D) method and the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) development model. The research results are interactive multimedia based on Problem-Based Learning (PBL) utilizing Google Sites, which can be accessed using various electronic devices. This multimedia focuses on trigonometry material for 10th-grade high school students by presenting problem orientation in the form of contextual problems and language that is easy for students to understand. The research results also show that the developed product has been revised several times to produce interactive multimedia that is worthy of testing and useful. The percentage of validity of the interactive multimedia from subject matter experts is 100% (very valid) and 98% (very valid) from design experts. The percentage of practicality of the interactive multimedia by educators is 86% (very practical) and by students 87% (very practical), the percentage of effectiveness of the interactive multimedia from student response questionnaires is 92% (very effective), and from learning outcome tests in the form of pre-tests and post-tests using N-Gain with 7 people in the medium category and 29 people in the high category.